COMT Gene Haplotypes Are Closely Associated with Postoperative Fentanyl Dose in Patients. (April 2015) - Zhang, Fan; Tong, Jianbin; Hu, Jie; Zhang, Hao; Ouyang, Wen; Huang, Dong; Tang, Qiuping; Liao, Qin
Abstract : BACKGROUND: Fentanyl's analgesic efficacy varies widely among individuals. The single-nucleotide polymorphisms (SNPs) of catechol- O -methyltransferase ( COMT ) modulate sensitivity to pain. It remains unclear, however, whether COMT genetic variability affects postoperative fentanyl analgesia in patients undergoing radical gastrectomy. METHODS: One hundred fifteen patients, ASA physical status I–III, who were scheduled for radical gastrectomy under general anesthesia, were enrolled in this study. Patient-controlled IV analgesia with fentanyl was administered during the first 48 hours after surgery. Visual analog scale score for patients' pain was maintained at ⩽30 mm. The amount of fentanyl consumed and side effects were recorded for the first 24 and 48 hours postoperatively. The SNPs of COMT (rs6269, rs4633, rs4818, and rs4680) of all patients were screened by DNA sequence analysis of polymerase chain reaction−amplified DNA or polymerase chain reaction-restriction fragment length polymorphism. RESULTS: There were no significant differences in the doses of fentanyl used among patients possessing different SNPs of COMT rs6269, rs4633, rs4818, and rs4680 at 24 (all P > 0.207) and 48 (all P > 0.148) hours after surgery. COMT gene haplotypes combined by COMT rs6269, rs4633, rs4818, and rs4680, however, significantly affected fentanyl consumption at 24 ( P = 0.029) and 48 ( P = 0.032) hours after surgery. Among the haplotypes of COMT gene, patients with haplotype ACCG consumed more fentanyl than GCGG and ATCA haplotypes during the first 24 and 48 hours (all P < 0.042) after surgery. No significant differences were found in the incidence of nausea, vomiting, and dizziness among the 4 SNPs of COMT gene (all P > 0.079) and their haplotypes (all P > 0.482). CONCLUSIONS: COMT gene haplotype constructed by rs6269, rs4633, rs4818, and rs4680 contributes to the individual variation of postoperative analgesia with fentanyl. Patients carrying the COMT gene haplotype ACCG consumed the most drug during the first 24 and 48 hours postoperatively. Abstract : Published ahead of print December 19, 2014